Examining the impact of factors that influence UUM students' intention to enroll in Master in Islamic Finance and Banking program - Nur Atikah, Mohmad Jumat (2014)
As nowadays the development of Islamic finance and banking continue to get much attention from the government, higher learning institution starts to offer more Islamic finance and banking course related in order to produce a quality human resource in the field. This study aims to inspect the student’s intention to enroll in Master in Islamic Finance and Banking (MIFB) program offered by Universiti Utara Malaysia (UUM). A survey comprised of 200 respondents was carried out. In addition, the use of personal factors, parental influence, financial aids, job opportunities, program quality, cost and religious motivation as the factors will help the researcher to find out the most factors that influence student’s intention to enroll in MIFB program. A structured question was designed where the data were analyzed by means of t-test, ANOVA, correlation and multi regression analysis. Results show that personal factors, parental influence, financial aids, job opportunities, program quality, cost and religious motivation are significantly important determinants to predict student’s intention to enroll in MIFB program. The result in multiple regression shows that the most influencing factors are personal factors, program quality and religious motivation. Therefore, the program provider should focus on the quality of the program by improving the quality of teaching and course provision. Lastly, they should also show the application of religious value provided by enrolling in MIFB program